The social terrain of endemic tuberculosis in and around Cape Town - Murray, Emma Jane (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Communicable Diseases)) (Dept of Interdisciplinary Health Sciences. Community Health))--University of Stellenbosch, 2010.